2016
DOI: 10.1021/acssuschemeng.6b01371
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Synthesis of Noroxymorphone via Aerobic Palladium-Catalyzed Continuous Flow N-Demethylation Strategies

Abstract: The palladium-catalyzed N-demethylation of the opioid alkaloids oxymorphone 3,14-diacetate and 14-hydroxymorphinone 3,14-diacetate to their nor-derivatives with oxygen as the terminal oxidant has been investigated. Palladium­(II) acetate forms colloidal palladium(0) particles upon heating in N,N-dimethylacetamide. The palladium(0) particles are effective catalysts for the aerobic N-demethylation of these opiate alkaloids. Demethylation of 14-hydroxymorphinone 3,14-diacetate with pure oxygen as oxidant in a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…The N-methyl group is contained in naturally occurring alkaloids (e.g., morphine, codeine, thebaine or oripavine) and its removal is needed to gain access to potent N-alklyated opioid receptor antagonists. In particular, the Pd-catalyzed aerobic N-demethylation of 14-hydroxymorphinone 3,14-diacetate was achieved using pure O 2 in a 100 mL stainless steel flow reactor on a 1 kg scale (Scheme 3) [35]. Prior to scale-up, micro-calorimeter (μRC) experiments and differential scanning…”
Section: Pd-catalyzed Reactionsmentioning
confidence: 99%
“…The N-methyl group is contained in naturally occurring alkaloids (e.g., morphine, codeine, thebaine or oripavine) and its removal is needed to gain access to potent N-alklyated opioid receptor antagonists. In particular, the Pd-catalyzed aerobic N-demethylation of 14-hydroxymorphinone 3,14-diacetate was achieved using pure O 2 in a 100 mL stainless steel flow reactor on a 1 kg scale (Scheme 3) [35]. Prior to scale-up, micro-calorimeter (μRC) experiments and differential scanning…”
Section: Pd-catalyzed Reactionsmentioning
confidence: 99%
“…The procedures produced a common advanced intermediate (noroxymorphone, 141 ) for the preparation of naloxone ( 142 , Figure ) and relied on pivotal alkene hydrogenation and N ‐demethylation reactions. For instance, the authors used 14‐hydroxymorphinone‐3,14‐diacetate ( 136 ) as a starting material (Figure ). They reported that colloidal Pd 0 particles were very effective catalysts for the aerobic N ‐demethylation of selected opiate alkaloids.…”
Section: Continuous Flow Preparation Of Active Pharmaceuticalsmentioning
confidence: 99%
“…Hydrocodone is listed as a Schedule II substance by the DEA. In a series of papers dealing with the continuous flow preparation of opioids, Kappe and co‐workers described a continuous flow process for the preparation of hydrocodone ( 252 ) from thebaine ( 250 ) (Figure ) . Selective olefin reduction formed 8,14‐dihydrothebaine ( 251 ), which was next hydrolyzed to yield 252 .…”
Section: Perspectivesmentioning
confidence: 99%
“…Recently, our group has developed a series of strategies for the generation of noroxymorphone ( 4 ) from 14‐hydroxymorphinone under continuous‐flow conditions . The crucial reaction step towards the generation of 4 was an unprecedented aerobic N ‐methyl oxidation using palladium(0) as catalyst, which generates oxazolidine 5 as intermediate (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Palladium(0) particles of high catalytic activity were generated by heating Pd(OAc) 2 in DMA/AcOH. With the 14‐ N ‐hydroxy opioids dissolved in this solution, a rapid and selective methyl oxidation to 1,3‐oxazolidines ensued in the presence of O 2 . The reaction, based on the original method developed by Hudlicky et al in 2008, consumes only O 2 as stoichiometric reagent and produces H 2 O as the only byproduct.…”
Section: Introductionmentioning
confidence: 99%